RELASI MASYARAKAT KAMPUS: SOSIAL ATAU INTELEKTUAL - Nufiar Nufiar (Universitas Islam Negeri Ar-Raniry, 2008)
In science tradition, usually, the relation of latent instructing in profetik-akademic doesn’t emerging off hand. He (she) must be woke up when needed given by opportunity which berkelindan as presentation of domination of self and increasing of quality. Hence, campus institute which is one of icon is place of accomodating various place meeting of antar-pikiran, and not meeting of antar-pribadi. Because, patron such a science, part of practice of idea discourse to be being animated in area of which